Survive, Learn, Thrive : Strategic Human Capital Investments Toward a More Prosperous and Inclusive Armenia - World Bank (World Bank, Washington, DC, 2020)
Human capital – the knowledge, skills, and health that people accumulate over their lives and that enable them to realize their potential as productive members of society – is an important contributor to the wealth of all nations regardless of their income status. A child born in Armenia today will be 57 percent as productive when she grows up as she could be if she received a full education and was completely healthy. This reflects the existence in Armenia of deficiencies in its schooling, student performance on harmonized tests, and the protection from non-fatal health risks that it provides beyond childhood. These gaps in human capital formation have negative implications for the economy. The 2013-2014 National Competitiveness Report of Armenia highlighted that insufficient human capital is a binding constraint to the country’s growth. If Armenia ensured full education and complete health in the long run, the per capita Gross Domestic Product could be 1.75 times higher.